Effects of dietary NDF/NFC ratios on in vitro rumen fermentation, methane emission, and microbial community composition - Li, Jichao; Guan, Feng; Liu, Pengyu; Ma, Huiting; Zhang, Jiyou; Ma, Yumin; Mao, Shengyong; Xiang, Xiao’e; Jin, Wei (Frontiers in Veterinary Science, 2025)
The objective of this study was to investigate the effects of dietary neutral detergent fiber (NDF) to non-fibrous carbohydrate (NFC) ratios on in vitro rumen fermentation, methane production, and microbiota in dairy cows. In vitro rumen fermentation was conducted with five dietary groups: R0.48 (NDF/NFC = 0.48), R0.57 (NDF/NFC = 0.57), R0.70 (NDF/NFC = 0.70), R0.90 (NDF/NFC = 0.90), and R1.12 (NDF/NFC = 1.12). As the NDF/NFC ratios increased, total gas production decreased linearly. The degradation rates of dry matter (DM), neutral detergent fiber (NDF), and acid detergent fiber (ADF) decreased, showing a quadratic response (p = 0.018). Methane production per unit of DM was not significantly affected (p > 0.05), whereas methane production per unit of degraded DM increased (p < 0.05). The concentrations of acetate, lactate, and the acetate-to-propionate ratio, as well as pH, increased linearly (p < 0.05), whereas the concentrations of propionate, isobutyrate, isovalerate, and total volatile fatty acids (TVFA) decreased linearly (p < 0.05). Microbial crude protein (MCP) production was greater in the low NDF/NFC groups (p = 0.003). Quantitative real-time PCR analysis revealed that anaerobic fungi were more abundant in the high NDF/NFC groups (p = 0.001), whereas bacterial and archaeal abundances did not differ significantly among groups (p > 0.05). Illumina MiSeq PE250 sequencing revealed that the alpha diversity of both bacterial and archaeal communities was influenced by NDF/NFC (p < 0.05). Principal coordinate analysis further indicated that composition of bacterial (R2 = 0.298, p = 0.001) and archaeal (R2 = 0.470, p = 0.001) communities differed significantly among groups. Differences in bacterial communities were primarily driven by Firmicutes (e.g., Ruminococcus, Pseudobutyrivibrio) and Proteobacteria (e.g., Succinivibrio, Ruminobacter), whereas variations in archaeal communities were associated with Methanobacteriales and Methanomicrobiales. In conclusion, increasing dietary NDF/NFC ratios led to higher methane production per unit of degraded DM, reduced nutrient degradation, and lower TVFA concentrations during in vitro rumen fermentation, accompanied by distinct shifts in bacterial and archaeal community composition.